Pengembangan Server VOIP Menggunakan FREEPBX Dan Asterisk Berbasis Raspberry PI - Nasron, Nasron; Mujur Rose, Martinus; Fadhilah, Darin (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
Raspberry Pi is a single board computer that the author uses as a voip server based on asterisk. To use this voip network, each device must have a static IP as well as be connected to a stable network. The advantage of using raspberry pi is that it no longer costs money to make voice calls for both package and pulse costs. The purpose and benefits of this research to know how raspi works, know how to install voip server using freepbx and asterisk, know how to install voip client on smartphones and laptops dang know the topology of raspi-based voip network, and know how to test stages of searching for throughput, loss package, delay, and jitter using wireshark